2008
DOI: 10.5713/ajas.2008.80074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xylanase on Growth and Gut Development of Broiler Chickens Given a Wheat-based Diet

Abstract: To study the working mechanisms for non-starch polysaccharidases to improve the growth performance of broiler chickens, a 21-day feeding trial was conducted. Two dietary treatments were included: 1) wheat diet (the control); 2) wheat+xylanase diet (xylanase, Allzyme PT, Alltech, Kentucky, USA). There were 8 replicates with 8 birds each for each treatment and the experimental diets were given to birds from hatch. Feed intake and body weight were measured on days 7 and 21. At the same ages, samples were taken fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
(36 reference statements)
3
16
0
5
Order By: Relevance
“…Over the past decade, many studies have reported that adding exogenous enzymes, like xylanase, to wheat-based diets may reduce the anti-nutritional effects of AX and consequently improve performance in poultry (Steenfeldt et al 1998;Engberg et al 2004;Meng et al 2005;Yang et al 2008). In this study, broiler chickens fed a wheat-based diet supplemented with exogenous endo-xylanases from 7 to 21 d of age showed significant increase of the final body weight and of the DWG during this period.…”
Section: Discussionmentioning
confidence: 59%
“…Over the past decade, many studies have reported that adding exogenous enzymes, like xylanase, to wheat-based diets may reduce the anti-nutritional effects of AX and consequently improve performance in poultry (Steenfeldt et al 1998;Engberg et al 2004;Meng et al 2005;Yang et al 2008). In this study, broiler chickens fed a wheat-based diet supplemented with exogenous endo-xylanases from 7 to 21 d of age showed significant increase of the final body weight and of the DWG during this period.…”
Section: Discussionmentioning
confidence: 59%
“…A similar observation in the present study was the lower colony counts of E.coli in diets with enzymes. Yang, Iji, Kocher, Mikkelsen, and Choct (2008) observed an increase in the number of coliforms and a reduction in the counts of lactobacilli with inclusion of xylanase in wheatbased diets. The chemical composition of the digesta has the influence on the composition of the gut microbial community because different bacterial species have different substrate requirements for growth (Apajalahti, Kettunen, & Graham, 2004)..…”
Section: Resultsmentioning
confidence: 91%
“…Additionally, crypt depth values indicate the proliferative activity of epithelial cells (Geyra et al 2001); low crypt depth values suggest reduction in the metabolic cost of intestinal epithelium turnover (Willing & Van Kessel, 2007). Yang et al (2008) verified that xylanase supplementation of diets based on wheat did not change villus height, but reduced jejunal crypt depth of 7-day-old broilers. Mathlouthi et al (2002) reported higher villus height and villus:crypt ratio in the ileum in 22-day-old broilers fed diets based on corn or wheat with inclusion of β-glucanase + xylanase compared with those fed the wheat-based diet with no enzyme supplementation.…”
Section: Performance and Morphometry Of The Intestinal Mucosa Of Layimentioning
confidence: 67%
“…Changes in the intestine by the presence of exogenous enzymes in diets tend to be small, but not only reduction in the size of the intestine and/or release of endogenous enzymes, but also increase of the villi are frequently observed, including in broilers (Yang et al, 2008). Additionally, crypt depth values indicate the proliferative activity of epithelial cells (Geyra et al 2001); low crypt depth values suggest reduction in the metabolic cost of intestinal epithelium turnover (Willing & Van Kessel, 2007).…”
Section: Performance and Morphometry Of The Intestinal Mucosa Of Layimentioning
confidence: 99%